PENGARUH MOTIVASI KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN KEPALA SEKOLAH (Studi pada Guru PAUD di UPT Dinas Pendidikan Kecamatan Pati) - 11.52.02.0091, Sri Hartami (Jurnal Mahasiswa Pasca Sarjana, 2013)
The research is for examining the effect of work motivation and teachers competent for teachers job moderation in leading headmaster (study of PAUD Teachers in UPT Dinas Pendidikan Kec. Pati ).The research is a quantitative research that used survey method by analysis descriptive. The method that used in this research is census where the same sample with the amount of population is 135 teachers, whereas the data that process is 177 teachers. The measuring used Likert Scale with 7 answers alternative. The instrument is using validity and reliability. Whereas, the model of this research is Determination Coefficient (R2) and F (Goodness of Fit). The hypothesis in this research is using Regressed analysis. Based on this research can be concluded ( i) the work motivation can be positive effect and significant for teachers job, (ii) teachers competent can not positive effect for teachers job, (iii) the leading of headmaster can not positive effect and significant for teachers job, ( iv) the leading of headmaster can improve the effect of teachers competent for teachers job. Key words : Work Motivation, Teachers Competent, Leading Headmaster and Teachers Job